P252 Does anodal tDCS of the premotor cortex enhance the effects of motor imagery on motor sequence learning?. Issue 3 (March 2017) - Saimpont, A.; Richard, O.; Chabaud, P.; Jackson, P.L.; Guillot, A.; Collet, C.
Abstract : Introduction: There is ample evidence that motor imagery (MI) training – i.e. the mental repetition of movements without corresponding actual execution – contributes to enhance motor performance. Such positive effects are greater when MI is accompanied by anodal tDCS applied over the primary motor cortex (Foerster et al., 2013; Saimpont et al., 2016). While the premotor cortex is known to be active during MI (Hetu et al., 2013), its role on motor performance improvement by MI training needs to be clarified. Objective: The main aim of this study was to examine whether anodal tDCS applied over the premotor cortex might enhance the effect of MI training on the learning of a finger tapping task. Materials and methods: The experiment was conducted in a double-blinded sham-controlled crossover design. Twelve right-handed young adults (mean age = 22.4 ± 2.5 years, 5 females) participated in two experimental sessions. During each session, participants performed MI training for 13 min combined either with anodal tDCS (current intensity = 1.5 mA, current density = 0.06 mA/cm 2 ) over the right premotor cortex (FC2 location in the 10–20 system), or with sham stimulation over the same region. Motor imagery training consisted in mentally rehearsing an 8-item complex finger sequence with the left hand. Before (Pretest) and immediately after (Posttest) MI training, participants physically repeated the sequence as fast and accurately as possible. Results showed a significant increase in the number of correct sequences after MI training in both conditions ( p  < .001, η 2  = .87); performance improvement was however not significantly different between conditions ( p  = .27, η 2  = .11); see Fig. 1. Interestingly, we found a significant correlation between performance improvements and self-reported levels of MI vividness during MI training in both conditions (real: R  = 0.68, sham: R  = 0.64); see Fig. 2. Conclusion: Results suggest that the positive effects of MI training on motor sequence learning do not primarily result from an increase in activity in the premotor cortex. More participants will confirm/ infirm these preliminary results.